Performance of isolated and folded footings. Issue 2 (14th September 2016) - El-kady, Mahmoud Samir; Badrawi, Essam Farouk
Abstract: Folded foundations have been used as an alternative to the conventional flat shallow foundations, in situations involving heavy loads or weak soils. They can be geometrically shaped in many forms especially for isolated footings. The purpose of this paper is introducing an alternative foundation shape that reduces the cost of foundations by reducing the amount of reinforcing steel by minimizing or even eliminating the tension zones in the folded isolated footings. Also, achieving lower soil stresses through changing the isolated footing shape will consequently reduce the expected settlements and the footing stresses. Experimental and numerical studies are performed on five (5) quarter scale footings of which one (1) footing of flat shape is tested as a reference sample and four (4) footings are of folded shape by folding angles of 10°, 20°, 30°, and 40° with the horizontal. Results showed that the folded isolated footings achieve economic design by decreasing the quantities of reinforcement. It also induced less soil settlements, and stresses. In addition, the tensile stresses in the reinforced concrete footing body are also less in folded isolated footings than the flat one. Results show that the folded isolated footing have a better load carrying capacity when compared with the conventional slab/flat footing of similar cross sectional area for both cases of experimental and numerical analysis. Graphical abstract: